Synthesis of Potassium Silicate Nanoparticles from Rice Straw Ash Using a Flame-assisted Spray-pyrolysis Method. (March 2017) - Nandiyanto, A B D; Permatasari, N; Sucahya, T N; Abdullah, A G; Hasanah, L
Abstract: The purpose of this study was to synthesize potassium silicate nanoparticles from rice straw ash using a flame-assisted spray-pyrolysis method. Rice straw, as one of the agricultural wastes, was used as a source of silica. In the experimental procedure, rice straw was burned at 700°C for 3 hours to produce rice straw ash. Then, the rice straw ash was extracted using an alkaline method. We used potassium hydroxide (KOH) as an alkaline chemical agent as well as a source of potassium. The solution was then put into the flame-assisted spray-pyrolysis apparatus to produce potassium silicate nanoparticles. The results showed that the spray method can assist the production of spherical potassium silicate nanoparticles with sizes of about 50 nm.